Open-Book Accounting in the Relationship Between the Cooperative and Cooperative Members in the Coffee Sector - Silva Lima, Daiane; Cristina Francisco de Almeida Fehr, Lara; Lemos Duarte, Sérgio; Luiz Borinelli, Márcio (Advances in Scientific and Applied Accounting, 2023)
Objective: To analyze how Open-Book Accounting (OBA) is practiced, considering its dimensions, in the relationship between a coffee cooperative and its members from the perspective of Transaction Cost Economics. Method: Case study of the relationship between a cooperative and its members. For data collection, semi-structured interviews, document analysis and direct non-participant observation were used. For the analysis, Content Analysis was used. Results/Discussion: It was verified that the OBA is applied bilaterally, with a high level of detail of information in the cooperative-cooperative sense and low level, in the opposite direction. The application conditions are based on cooperation and trust, contemplating incentives and the prediction of mutual benefits. It was noticed that the transaction costs of the analyzed relationship are reduced, because, a priori, both the cooperative and the members do not perceive opportunism in the use of shared information. It is concluded that the relationship studied favors the application of OBA, since it is based on cooperation, one of the main pillars for its effective application and generation of potential benefits. Contributions: The study expands knowledge in the areas of Administration and Accounting by researching the application of OBA in cooperatives. It contributes to practice by making it possible to understand the application of the OBA and its strengths and weaknesses in cooperativism. It generates social contribution, since the proper management of costs, based on the sharing of information, enables superior performance in the cooperatives’ businesses and income generation for the families involved.